Desarrollo de habilidades lectoras en sujetos sordos signantes, a partir del uso de códigos dactílicos (Educational Perspectives Magazine (REPED), 2023)
This study focused on the exploration of the codes of linguistic information processing in deaf students who use the Chilean Language of Signs fforn the early ages. Thirty students ofthe ages of 7 to 17 were included in the sample. The research results show a significant correlation between the level of mastering the language of signs, the ability for fmgerspelling and that of reading. The ñndings of the study allow indicate the need to use these visual codes to improve the teaching of reading for deaf students.
Keywords: Deafhess, sign language and fmgerspelling.